Eco‐sustainable silk sericin from by‐product of textile industry can be employed for cosmetic, dermatology and drug delivery. Issue 9 (11th May 2020) - Orlandi, Giulia; Faragò, Silvio; Menato, Silvia; Sorlini, Marzio; Butti, Fabrizio; Mocchi, Michela; Donelli, Ilaria; Catenacci, Laura; Sorrenti, Milena L; Croce, Stefania; Segale, Lorena; Torre, Maria L; et al.
Abstract: BACKGROUND: In the last decade, many researchers demonstrated the biological activities of native Bombyx mori silk sericin (SS), and its use is widespread in the cosmetic and biomedical field. However, SS is a polluting material from the silk fibroin textile industry. This paper aims to demonstrate that the industrial wastewater‐derived SS has many biological properties, and can be used as an eco‐friendly product for cosmetic/pharmaceutical purposes with an important impact on the circular economy. RESULTS: We focused on the SS derived from an ad hoc extraction process or industrial degumming wastewater. Both products were preserved with three different methods: lyophilization, spray‐drying and sterilization. All SS were characterized in terms of amino acid content, molecular weight, physical–chemical properties, morphology and size distribution; then we evaluated the biological properties, the cytocompatibility/cytoprotective profile, and the immunomodulatory abilities of SS. Free radical scavenging, anti‐tyrosinase, and anti‐elastase activities of waste SS were confirmed. Waste and standard SS were cytocompatible on human fibroblasts; all SS samples inhibited the proliferation of stimulated peripheral blood mononuclear cells in a dose‐dependent manner. Waste SS showed a significant effect on tumor necrosis factor α and interleukin 10 release. CONCLUSIONS: These results pave the way for using textile wastewater‐derived SS to obtain high‐value‐added products for cosmetic and/or pharmaceutical purposes. © 2020 Society of Chemical Industry